El docente como formador ético - Narváez Rivero, Miryam (2015)
The present article cover the latent preoccupation in the last years about the ethical formation of the teacher in relation to the “crisis of values” in which we live in. The topic will be approached giving a general view of what is and what isn’t the ethical formation of the university professor. In this sense, it tries to analyze in which ways the concepts of ethics and citizenship are installed in the professor’s speech, but do not manage to manifest themselves effectively in the schools. We will analyze the concept of ethical formation as a process of collective construction, which demands the preparation and exercise of critical reflection, just like the taking of decisions about moral situations that regulate the coexistence between the actors in the educational process (students, professors, administrative personnel, etc.) We will reflect on the role of the professors as people and ethical educators. The professors’ formation demands a compromise with themselves, in which they can develop a responsible job that allows them to know themselves better as human beings, in such a way that they are able to manage at a conscious level their ideas, affections and emotions. The exigency of the educational process demands that it should be, in essence, conversational and with dialogue, in which active listening should be a fundamental part of it. Likewise, some of the principal ethical qualities that a professor should have and demonstrate will be revised. Finally, some moral messages and strategies for the ethical formation in the classroom will be analyzed, based on the fact that every educational interaction is filled with a lot of moral connotations, of which the professors have to be conscious in order to be able to contribute to the ethical growth of their students.